Composition dependences of crystal structure and electrical properties of epitaxial Pb(Zr, Ti)O3 films grown on Si and SrTiO3 substrates. (9th September 2016) - Okamoto, Shoji; Okamoto, Satoshi; Yokoyama, Shintaro; Akiyama, Kensuke; Funakubo, Hiroshi
Abstract: 100-oriented Pb(Zr x, Ti1− x )O3 (PZT) thin films of approximately 2 µm thickness and Zr/(Zr + Ti) ratios of 0.39–0.65 were epitaxially grown on (100)c SrRuO3 //(100)SrTiO3 (STO) and (100)c SrRuO3 //(100)c LaNiO3 //(100)CeO2 //(100)YSZ//(100)Si (Si) substrates having different thermal expansion coefficients by pulsed metal–organic chemical vapor deposition (MOCVD). The effects of Zr/(Zr + Ti) ratio and type of substrate on the crystal structure and dielectric, ferroelectric and piezoelectric properties of the films were systematically investigated. The X-ray diffraction measurement showed that both films changed from having a tetragonal symmetry to rhombohedral symmetry through the coexisting region with increasing Zr/(Zr + Ti) ratio. This region showed the Zr/(Zr + Ti) ratios of 0.45–0.59 for the films on the STO substrates that were wider than the films on the Si substrates. Saturation polarization values were minimum at approximately Zr/(Zr + Ti) = 0.50 for the films on the STO substrates, and no obvious Zr/(Zr + Ti) ratio dependence was detected in the films on the Si substrates. On the other hand, the maximum field-induced strain values measured by scanning force microscopy at approximately Zr/(Zr + Ti) = 0.50 at 100 kV/cm were about 0.5 and 0.1% in the films on the Si and STO, respectively.